KEANEKARAGAMAN SPESIES AVIFAUNA DIURNAL DI BEBERAPA TIPE HABITAT PADA AREAL IUPHHK-HTI PT HUTAN KETAPANG INDUSTRI KABUPATEN KETAPANG - Dwifortunata, Tomy; Prayogo, Hari; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2020)
Birds or Aves are members of vertebrates that have feathers and wings. Spreads from lowlands until highlands occupying various habitats, similarly in Kalimantan birds are found in various places. The goal of this research is to acquire biodiversity data of birds in certain types of the forest before and after operations in the region of PT Hutan Ketapang Industri. This research use the IPA (Index Point Abundance) method which is placed purposively on five types of habitat. The habitats are kerangas forest, peat swamp forest, dipterocarpus lowland forest, riparian and open wetland/flood plain. The research was conducted in the area before and after operational activity. The research shows the differences in results at each location. There are found 40 species of birds that belong to 23 families. Â Â Keyword: Bird Diurnal, Diversity, Five Habitat Types